A Digital Illustrated Storybook Containing Local Wisdom of Traditional Balinese Food to Improve Science Literacy - Ni Luh Nyoman Wina Wahini; I Gede Margunayasa; I Wayan Kertih (LPPM Undiksha, 2026)
Science learning in grade IV of elementary school is still not aligned with students' cognitive development at the concrete operational stage, due to the dominance of theoretical approaches and the lack of contextual and meaningful learning materials. These conditions contribute to low scientific literacy. The purpose of this study is to create a digital picture storybook featuring local wisdom on traditional Balinese food as a learning medium to improve scientific literacy. This type of research is Research and Development (R&D) using the ADDIE model. The research subjects used 2 learning media experts and 2 learning material experts. The practicality test was carried out by 3 educators/teachers and 10 students. The effectiveness test was carried out with 30 participants. The data collection method used tests and questionnaires. The instruments used were questionnaire sheets and test questions. The analysis techniques used in this study were qualitative and quantitative. The results of the study, namely the developed digital picture storybook, were deemed highly valid based on assessments by media and material experts. The results of the practicality test were very high, as indicated by 96.75% of teacher responses and 92.75% of student responses. The effectiveness test indicated a significant difference in students' scientific literacy before and after using digital picture storybooks featuring local wisdom about traditional Balinese food. It was concluded that picture storybook media were effective in improving elementary school students' scientific literacy.